Experiences of Undergraduate Nursing Students on Clinical Placement as a Formal Community of Practice - Schembri, Neville (Advances in Social Sciences Research Journal, 2024)
Background: Through their academic journey at their academic institutions and clinical practice placements, nursing students experience mutual engagement, joint enterprise, and a shared repertoire that marks a community of practice. As a result of this interaction and activity, students develop an interprofessional identity as they also become active members of this interprofessional community. Method: A descriptive qualitative approach was used to study the experience of 12 student nurses following clinical practice placements. Purposive sampling was adopted and the data from individual interviews was analysed using thematic analysis. Results: Five themes emerged, namely: Bridging the Theory-Practice Gap, Feeling Welcomed and Wanted, Belongness and Support, Chance of Being Selected and Need for Further Collaboration. Conclusion: Through practical placements and engagement with other healthcare professionals, the student’s ability to utilize interpersonal skills and professional skills are highly developed and by becoming part of a community of practice, they develop to become an essential asset in today’s health workforce.